Corticospinal potentials after transcranial stimulation in humans. Issue 8 (August 1989) - Inghilleri, M; Berardelli, A; Cruccu, G; Priori, A; Manfredi, M
Abstract : The descending volley evoked in humans by transcranial electrical stimulation of the scalp was recorded with epidural and spinal electrodes. It consisted of an early wave, which increased in amplitude and decreased in latency when the strength of the stimulus was increased. The mean conduction velocity of the early wave was 66, SD 2.5 m/s. At high stimulus intensity this wave was followed by later and smaller waves, which travel at the same speed as the initial potential. The recovery cycle of the descending volley was studied by delivering paired cortical stimuli at time intervals ranging from 0.5 to 10 ms. The early wave evoked by the test stimulus recovered to about 50% at a 1 ms interval and to 100% at a 3.5 ms interval. The later waves could not be tested at short time intervals but with time intervals longer than 3.5 ms they recovered to 100%. It is suggested that the initial and later waves after scalp stimulation are equivalent to the D and I waves seen in animal experiments.